(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Under normal conditions, bile in a healthy person is sterile; however, when contaminated with microbes, E. coli and Enterococcus are found in 70–80% of cases, while K. pneumoniae, Enterobacter, and, less frequently, Salmonella species may also be present. Among anaerobic microorganisms, Clostridium perfringens can be detected, and representatives of the Peptococcaceae family occur in 10–20% of cases of gallstone disease. In some instances, mixed aerobic and anaerobic infections may also develop. Clostridium perfringens can lead to sepsis by producing more than 15–20 different types of toxins, including α-toxin, which causes hemolysis (the destruction of red blood cells) and is associated with a very poor prognosis. In animals, C. perfringens is the primary cause of necrotic enteritis and traumatic gangrene. In certain cases, this bacterium may also cause acute gas-forming cholecystitis (emphysematous cholecystitis) in patients with biliary tract infections. However, co-infection of C. perfringens with other aerobic bacteria (such as E. coli) resulting in bacteremia is extremely rare and most often ends fatally.